Analisis Kemampuan Mahasiswa dalam Menyelesaikan Soal Pembuktian tentang Isomorfisma Grup - Asyhar, Beni (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
Group Isomorphism is one of the sub topic in the Algebra Structure. This sub topic required prerequisite material about the bijective function. If this prerequisite material is not mastered, it will be difficult to study Isomorphism Group material. There are still many students who found difficulties to solve probative questions about Group Isomorphism. The major problem are they were forgetting and not understanding the prerequisite material. Therefore, it should be a further research on the ability of students to prove the questions of proof and errors in preparing evidence about Group Isomorphism.